2020
DOI: 10.1002/ana.25669
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing Patient Selection for Endovascular Treatment in Acute Ischemic Stroke (SELECT): A Prospective, Multicenter Cohort Study of Imaging Selection

Abstract: Objective The primary imaging modalities used to select patients for endovascular thrombectomy (EVT) are noncontrast computed tomography (CT) and CT perfusion (CTP). However, their relative utility is uncertain. We prospectively assessed CT and CTP concordance/discordance and correlated the imaging profiles on both with EVT treatment decisions and clinical outcomes. Methods A phase 2, multicenter, prospective cohort study of large‐vessel occlusions presented up to 24 hours from last known well was conducted. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 29 publications
4
74
0
1
Order By: Relevance
“…The second HERMES metanalysis provided preliminary data suggesting that carefully selected patients with large cores (ASPECTS 3-5) may have more favorable functional outcomes despite an increased risk of ICH 14 . In line with these results, the SELECT trial 15 showed that in patients with unfavorable CT/favorable CTP, thrombectomy was associated with a reduction in mortality compared to medical management with similar safety outcomes regarding sICH. There are clinical trials underway to clarify this issue, in which after our results, the darkness of the ischemic core could be assessed together with core volume to evaluate its relative contribution to bleeding risk in this particular subset of EVT patients.…”
Section: Discussionmentioning
confidence: 67%
“…The second HERMES metanalysis provided preliminary data suggesting that carefully selected patients with large cores (ASPECTS 3-5) may have more favorable functional outcomes despite an increased risk of ICH 14 . In line with these results, the SELECT trial 15 showed that in patients with unfavorable CT/favorable CTP, thrombectomy was associated with a reduction in mortality compared to medical management with similar safety outcomes regarding sICH. There are clinical trials underway to clarify this issue, in which after our results, the darkness of the ischemic core could be assessed together with core volume to evaluate its relative contribution to bleeding risk in this particular subset of EVT patients.…”
Section: Discussionmentioning
confidence: 67%
“…Patients with favorable CT but unfavorable CT perfusion profiles had lower functional independence and high rates of symptomatic ICH, neurological worsening, and mortality. 137 A recent commentary of the SELECT2 Investigators meticulously delineates the uncertainty behind simple neuroimaging for patients with larger cores and is relevant for the debate for extended time windows. 138 Using the Alberta Stroke Program Early CT score (ASPECTS) to estimate established infarction is a strategy appearing simple but in practice is prone to errors; even after ASPECTS training, one in three readings from neuroradiologists resulted in misclassification (ASPECTS 0–2 versus 3–5 versus 6–8) in 20 illustrative cases.…”
Section: Endovascular Treatment In the Anterior Circulation Before And After 6 H From Lswmentioning
confidence: 99%
“…"The Optimizing Patient Selection for Endovascular Treatment in Acute Ischemic Stroke (SELECT): a Prospective Multicenter Cohort Study of Imaging Selection" 22 enrolled patients with stroke attributable to large-vessel occlusion who were treated with endovascular thrombectomy plus medical management or medical management alone, based on CT or CTP findings, up to 24 hours from the point that they were last known to be well at 9 comprehensive stroke centers across the United States. The decision to proceed with EVT vs medical management alone was made at the discretion of the local investigators in a nonrandomized fashion.…”
Section: Study Populationmentioning
confidence: 99%
“…We sought to assess EVT cost-effectiveness by performing a cost-effectiveness analysis for EVT as compared to medical management only (MM) using outcomes in patients with large ischemic core infarcts on CT (ASPECTS <6), CTP (rCBF <30% volume ≥ 50 cm 3 ) or both from the SELECT study, a prospective, multicenter cohort study of imaging selection 22 .…”
Section: Introductionmentioning
confidence: 99%